Use of an Antisense RNA Strategy To Investigate the Functional Significance of Mn-Catalase in the Extreme Thermophile Thermus thermophilus - Moreno, Renata (American Society for Microbiology, 2004)
The expression of an antisense RNA revealed that an Mn-catalase was required in Thermus thermophilus for aerobic but not for anaerobic growth. The antisense system is based on the constitutive expression of a “bicistronic” transcript consisting of the kanamycin resistance gene mRNA followed by the antisense RNA against the selected target.